Underivatized amino acids detection by anion-exchange chromatography coupled to a nanostructured detector - da Silva, José Luiz [UNESP]; Delfino, José Rodrigues [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2021)
This work reports the development of a fast and reliable amperometric sensor for the detection of amino acids. The detector was constructed using copper nanoparticles (CuNPs) supported on reduced graphene oxide (RGO) modified glassy carbon electrode (CuNPs-RGO/GCE) and based on the application of high performance anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD). Under optimized isocratic HPAEC-PAD conditions (using 40 mmol L−1 NaOH as mobile phase, flow rate of 0.30 mL min−1 and detection potential of 0.45 V vs. Pd/PdO), the linear dynamic ranges of the concentration of amino acids obtained were 0.50–50 µmol L−1 for lysine, 1.0–100 µmol L−1 for alanine, glycine and serine, and 5.0–100 µmol L−1 for leucine. The limits of detection (S/N = 3) obtained ranged from 0.10 (for lysine and leucine) to 0.50 µmol L−1 (for alanine, glycine and serine) and sensitivity varied from 6.1 (for leucine) to 21.5 nA µmol−1 L (for serine). The average recovery percentages ranged from 97% (for glycine) to 102% (for leucine and serine). The results obtained showed that the CuNPs-RGO/GCE has good long-term stability, repeatability and reproducibility; this makes the device suitable for application as an electrochemical detector. The successful application of the proposed method for the analysis of sugarcane vinasse demonstrates its suitability for separation and determination of amino acids in complex matrices.
Keywords: Amino acids; Copper nanoparticles; Modified electrode; Pulsed amperometric detection; Reduced graphene oxide; Sugarcane vinasse